STUDY OF LAMBERT STRETHER, THE HERO IN THE NOVEL THE AMBASSADORS BY HENRY JAMES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2018)
Lambert Strether is the editor of a green - covered review, subsidized by a widow, Mrs. Newsome of Woollett, Massachusetts. The main action of the story centres round his mission to bring home Mrs. Newsome's son Chad from Paris. He has been deputed by Mrs. Newsome with the task of saving her son from the clutches of a bad and immoral woman in Paris. As Mrs. Newsome's ambassador, his duty is to bring Chad back to his home and his family business at Woollett. If he accomplishes this mission successfully, he is assured of a secure and comfortable life in New England as Mrs. Newsome will reward him by getting married to him.